Assessing Geometrical Measurement Skills Among Year Five National School Pupils - Nasser, Siti Nur Annisa Mohd (2022)
Geometrical measurement is an important topic in mathematics that serves as the foundation for other disciplines such as physics, chemistry, biology, and geography. Furthermore, geometrical measurement has been introduced to pupils since the first year of primary school and is assessed in international and public examinations. However, geometrical measurement is reported to be one of the most challenging topics in primary mathematics since most pupils have inadequate understanding due to the learning practice of memorizing formulas without grasping the underlying concepts. Research has shown that factors of low understanding of geometrical measurement is due to the lack of assessment of geometrical measurement skills. Therefore, this study is conducted to develop an assessment framework and Geometrical Measurement Skills Instrument (GMSI) to assess Year Five pupils’ geometrical measurement skills. GMSI was developed by applying SOLO Taxonomy in the super item format, that emphasizes the hierarchical level of complexity of the items in order to ensure that the instrument covers both surface and deep level items. Data from 500 pupils were collected and analyzed quantitatively using Rasch analysis to examine the psychometric properties, profile the items in GMSI and identify the gender differences. 20 pupils were purposively selected for the qualitative analysis using thematic analysis to validate the assessment framework and identify the error patterns. The results revealed that GMSI met the psychometric properties, and the assessment framework's descriptors appeared to agree with the pupils' responses, indicating that GMSI is valid and reliable.